Students’ Perceptions of Using Machine Translation Tools In the EFL Classroom - Sujarwo Sujarwo (LP2M IAIN Sultan Amai Gorontalo, 2020)
Machine Translation (MT) refers to automatically trying to translate words, phrases, text, or speech from one language to another (Arnold et al., 1994). This study aims to analyze English as Foreign Language (EFL) students’ perceptions on utilizing machine translation (MT) in translating words, phrases, text, or speech. This research used descriptive qualitative method, 13 EFL students as respondents using this type of technology were described and analyzed. Data were gained from the analysis of the translation quality supported by machine translation procedures and questionnaires to 13 English students in translation subject. The results showed that, EFL students in the sixth and seventh semester of English education department of Megarezky University in translating words, phrases, texts, paragraphs had to recheck and rearrange to get a good translation by their own understandings. Machine Translation (MT) becomes another option to recognize the meaning of foreign language. Machine Translation can be used as dictionary as well. MT is incredibly useful and helpful, it can provide a general description to the users, it gives an inspiration or consideration to the users to understand the meaning.